Analysis of Grammatical Errors in the Writing of the Eleventh Grade Students at SMA Labschool UNTAD Palu - Muh Zakkaria; Konder Manurung; Siska Bochari; Hastini Hastini (Journal of General Education and Humanities, 2025)
The study aimed to investigate errors in students’ writing assignments and identify which errors students committed most often. This research was prompted by the fact that students in SMA Labschool UNTAD Palu struggle with the simple past tense as a language feature in recount texts. Utilizing a descriptive quantitative design, the study involved 15 students as the sample. Using the Surface Strategy Taxonomy by Dulay, Burt, and Krashen as a guide, it was shown that students commit all types of grammatical errors. Misformation was committed the most with a total of 127 occurrences (80,89%). Omission ranked second with 20 appearances (12,74%), followed by addition errors with 9 appearances (5,73%), and misordering ranked last with only 1 appearance (0,64%). The high number of misformation errors indicated that students were struggling to form correct verb tenses and to choose the correct word form. This suggests that students’ understanding of English morphology and tense usage is inadequate, especially in forming sentences with past-tense verbs.